Single-Channel Seismic Images from the Southern Indian Ocean acquired during the R/V Robert D. Conrad expedition RC0802 (1964) (IEDA: Marine-Geo Digital Library, 2004)
This data set was acquired with the LDEO Single-Channel Seismic system during R/V Robert D. Conrad expedition RC0802 conducted in 1964 (Chief Scientist: Dr. George Bryan). These data files are of JPEG format and include Single-Channel Reflection Seismic images that have not been processed after acquisition.